การพัฒนาเครือข่ายด้านการผลิตและการตลาดหอมแดง ของเกษตรกรในตำบลทุ่งยั้ง อำเภอลับแล จังหวัดอุตรดิตถ์ Network Development for the Marketing and Production for Shallot Farmers in Tungyung Sub-district, Lablae District, Uttaradit Province, Thailand - Yuphin Thuansri ยุพิน เถื่อนศรี (Journal of Social Development and Management Strategy, 2016)
การวิจัยครั้งนี้เป็นการศึกษาศักยภาพ ปัญหาความต้องการพัฒนา และสร้างกระบวนการ พัฒนาเครือข่ายด้านการผลิตและการตลาดหอมแดงของเกษตรกรตำบลทุ่งยั้ง อำเภอลับแล จังหวัดอุตรดิตถ์ ใช้วิธีวิจัยแบบผสมผสาน ประชากร คือ เกษตรกรผู้ผลิตหอมแดง ตำบลทุ่งยั้ง อำเภอลับแล จังหวัดอุตรดิตถ์ จำนวน 78 คน กลุ่มเป้าหมาย ได้แก่ แกนนำเกษตรกร ตัวแทนภาครัฐ จำนวน 30 คน เครื่องมือเป็นแบบสอบถาม แนวคำถามสนทนากลุ่ม วิเคราะห์ข้อมูลเชิงปริมาณโดยการแจกแจงความถี่และหาค่าร้อยละ ข้อมูลเชิงคุณภาพใช้การวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1) ศักยภาพด้านการผลิตของเกษตรกรดีกว่าด้านการตลาด โดยมีผลผลิตต่อไร่สูงและมีคุณภาพดี ส่วนศักยภาพด้านการตลาดอยู่ในระดับต่ำ เนื่องจากเกษตรกรไม่มีอำนาจในการต่อรองราคา จำหน่ายผลผลิตผ่านพ่อค้าคนกลาง โดยไม่มีการแบ่งเกรด 2) ปัญหาที่พบมี 2 ด้าน ดังนี้ ด้านการผลิต ได้แก่ เกษตรกรผู้ปลูกมีจำนวนลดลง ผลผลิตต่อไร่ลดลง และต้นทุนการผลิตสูง ด้านการตลาด ได้แก่ ราคาผลผลิตกำหนดโดยพ่อค้าและตกต่ำ และเกษตรกรต้องการพัฒนาให้มีการผลิตหอมแดงปลอดสารเคมี 3) ผลการพัฒนาเครือข่ายมีดังนี้ เกษตรกรจดทะเบียนกลุ่มจำนวน 42 ราย โดยได้เข้าอบรมเพื่อลดต้นทุนการผลิตและการเข้าสู่มาตรฐานการผลิตอาหารปลอดภัย มีการแลกเปลี่ยนเรียนรู้กับหน่วยงานภายนอกอย่างต่อเนื่อง ส่วนข้อเสนอแนะเชิงนโยบายหน่วยงานภาครัฐควรมีการหนุนเสริมด้านการผลิตและการตลาดอย่างจริงจังและต่อเนื่อง The aims of this research were to study shallots farmers’ produce and market potential, and their problems and needs, in order to develop their production and marketing and to develop a farmers’ network for production and marketing in Tungyung Sub-district, Lablae District, Uttaradit Province in Thailand. The population consisted of 78 shallot farmers in that area. The target groups were 30 farmer leaders and government representatives. The tools consisted of a questionnaire and focus group discussion guidelines. Statistics included frequency, percentage, and content analysis. The results revealed the following. 1) The potential for shallot production was better than seen in the marketing. The shallot yield per rai was high and of good quality; however, the potential for shallot marketing was at a low level because the farmers did not know the standard prices—they sold shallots in bulk without grading through middlemen. 2) There was a production problem in terms of the reduction of the number of shallot farmers, the reduction of yield per rai, and higher production costs. The problem of marketing was that the yield prices were fixed by middlemen and at a low level. 3) The results of network development included a group of 42 registering farmers that were trained to reduce production costs and to prepare for standardized safe food production through continuous sharing of knowledge and experience with external agencies. Provincial agricultural extension officers and commercial extension officers should encourage farmers to produce and market their shallots practically and continuously.